The Role of Islamic Religious Education in Character Development at Dayah Mahyal Ulum Al-Aziziyah, Aceh Besar Regency - Faisal Ali (Wasatha: Jurnal Studi Islam dan Humaniora, 2026)
Islamic Religious Education plays a crucial role in shaping and fostering students’ moral character, particularly within Islamic boarding schools (dayah). This study aims to analyze the role of Islamic Religious Education in character development among students at Dayah Mahyal Ulum Al-Aziziyah, Aceh Besar Regency. The research employs a qualitative descriptive method with a field study approach. Data were collected through observation, interviews, and documentation involving teachers, dayah leaders, and students. The findings indicate that character development at Dayah Mahyal Ulum Al-Aziziyah is implemented comprehensively through both formal and non-formal learning activities, such as classical Islamic studies, worship practices, and the habituation of discipline, responsibility, and politeness. Islamic Religious Education serves not only as a subject but also as a value system integrated into all aspects of students’ daily lives. Supporting factors in moral development include teachers’ exemplary behavior, a religious environment, and continuous supervision, while inhibiting factors include the influence of digital media and students’ family backgrounds. Therefore, Islamic Religious Education at this dayah has proven effective in instilling moral and spiritual values that shape students into individuals with noble character (akhlaqul karimah).